A New Species of Radula (Radulaceae, Porellales) From Mid‐Cretaceous Kachin Amber - Xiangbo Song; Wen Ye; Zixi Wang (Ecology and Evolution)
ABSTRACT The liverwort genus Radula, one of the largest genera within the order Porellales, is phylogenetically isolated and widely distributed, with many species thriving as epiphytes in diverse ecosystems. Fossil records of Radula are scarce, particularly those with sufficient morphological details for precise taxonomic assignment. In this study, we describe and illustrate a new species, Radula kachinensis sp. nov., from mid‐Cretaceous Kachin amber in Myanmar. The fossil exhibits a unique combination of diagnostic features, including broad lobules, short keels, and amentulose axes, with amentulose shoots producing 1–2 additional amentulose shoots. The new discovery sheds light on species diversity during the Cretaceous and offers deeper insights into the morphological traits of this liverwort genus.